2020
DOI: 10.1021/acs.jpcc.0c03988
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hydrodeoxygenation of m-Cresol to Toluene over Bifunctional NbOx–Pt

Abstract: This study compared the hydrodeoxygenation (HDO) of m-cresol over Pt and NbO x -modified Pt catalysts. Reactivity measurements demonstrated that Pt supported on carbon (Pt/C) has moderate selectivity for the production of toluene during the HDO of m-cresol, with a range of ring saturation products also being produced. The modification of Pt with niobium (NbO x –Pt/C), however, was found to enhance the selectivity to toluene to 95%. Temperature-programmed desorption, X-ray photoelectron spectroscopy, and high-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, this bio-oil must be processed and deoxidized for further upgrading before being used as fuels. Catalytic hydrodeoxygenation (HDO) is an effective approach for bio-oil upgrading. The physicochemical properties of upgraded bio-oil can be improved, such as the water content, total acid number, viscosity, and calorific value. , The types of catalysts and operating conditions result in various reactions occurred during the HDO process, such as direct deoxygenation via dehydroxylation, aromatic ring saturation through hydrogenation, and/or C–C bond cleavage by hydrogenolysis, which consume a large amount of H 2 and produce mixed products. , In recent years, researchers have extensively studied the selective HDO of biomass-based phenolic compounds to produce aromatic products (i.e., benzene, toluene, and xylene, BTX) under mild reaction conditions (low pressure and mild temperature). BTX are important raw materials in the organic chemical industry, which can be widely used in fuel additives, solvent resins, and dyes. This transformation can not only obtain high value-added products but also greatly reduce the consumption of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this bio-oil must be processed and deoxidized for further upgrading before being used as fuels. Catalytic hydrodeoxygenation (HDO) is an effective approach for bio-oil upgrading. The physicochemical properties of upgraded bio-oil can be improved, such as the water content, total acid number, viscosity, and calorific value. , The types of catalysts and operating conditions result in various reactions occurred during the HDO process, such as direct deoxygenation via dehydroxylation, aromatic ring saturation through hydrogenation, and/or C–C bond cleavage by hydrogenolysis, which consume a large amount of H 2 and produce mixed products. , In recent years, researchers have extensively studied the selective HDO of biomass-based phenolic compounds to produce aromatic products (i.e., benzene, toluene, and xylene, BTX) under mild reaction conditions (low pressure and mild temperature). BTX are important raw materials in the organic chemical industry, which can be widely used in fuel additives, solvent resins, and dyes. This transformation can not only obtain high value-added products but also greatly reduce the consumption of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Pt plays a significant role in stabilizing oxygen vacancies. Chen et al [15b] . prepared a NbO x ‐Pt bifunctional catalyst for use in HDO of m ‐cresol.…”
Section: Design Methods and Effects Of Oxygen Vacancies In Hdomentioning
confidence: 99%
“…The authors emphasized that this type of adsorption is different from that commonly reported for Pt catalysts, in which there is the adsorption of the aromatic ring with the metal surface, facilitating hydrogenation of the ring to produce saturated hydrocarbons. In this regard, it was concluded that the greater selectivity to toluene for the catalyst NbOx -Pt/C is justified mainly by the adsorption mechanism favored by this material, which induces C-O bond cleavage and hinders aromatic ring hydrogenation (T. Chen & Vohs, 2020). Ru catalysts supported on various materials containing niobium, such as phosphate and niobia, were also synthesized and tested for the production of cyclohexane from hydrodeoxygenation of anisole, in a dense and complete work developed by Zhao et al (2020).…”
Section: Figure 5 -Mechanisms Of Hdo Reactions Of Substituted Phenolic Compounds On Pd Catalystsmentioning
confidence: 99%
“…Furthermore, stability tests were also performed showing the good recyclability and stability of the catalyst. Hence the presented one-pot process over Pt/NbOPO4 catalyst seems to be a potential alternative for biofuels production from raw biomass (T. Chen & Vohs, 2020).…”
Section: Thermochemical Processes For the Production Of Bio-oil And Biocrudementioning
confidence: 99%